Perancangan Sistem Informasi Penyediaan Logistik di Biro Umum Menggunakan Metode Waterfall - Putri, Utami Mizani; Zaini, Ilham Mahda Zulfa; Oktaviani, Nur Riska Zulvi; Hikmah, Annisa Nurul; Salsabila, Syabina; Afriandi, Naufal; Susilawati, Susilawati (Prodi Bisnis Digital Universitas Pahlawan Tuanku Tambusai, 2025)
This report discusses the design of a logistics information system at the General Bureau of Jambi Province with the aim of improving the efficiency and effectiveness of logistics management, which was previously conducted manually. Issues such as process delays, data inaccuracies, and difficulties in tracking goods served as the main background for the system development. To address these problems, the Waterfall method was adopted due to its systematic and structured approach. The research was conducted through observation, interviews, and documentation during a four-month internship at the relevant institution. The result of this practical work is a proposed information system that covers the entire logistics process, from planning and procurement to distribution. With an integrated system, the General Bureau is expected to enhance data accuracy, speed up decision-making, and improve transparency and accountability in logistics management. This system design is expected to be a stepping stone toward digital transformation within the local government environment.